METHODOLOGY FOR FORMING KEY COMPETENCES BASED ON DIGITAL TECHNOLOGIES (Universal International Scientific Journal, 2026)
This article discusses the importance of teachers' competence in organizing the educational process in a qualitative and effective manner by integrating interactive methods, artificial intelligence tools, digital resources, various applications, and modern technologies into their teaching processes.
Keywords: competence, artificial intelligence, digital technology, information literacy, International Assessment Programs, Hemis, E-maktab, kundalin.com, summative assessment, BSB, CHSB, demo test.